Prevalence of Antibiotic Resistance Genes in Differently Processed Smoothies and Fresh Produce from Austria - Sonia Galazka; Valerie Vigl; Melanie Kuffner; Irina Dielacher; Kathrin Spettel; Richard Kriz; Norbert Kreuzinger; Julia Vierheilig; Markus Woegerbauer (Foods)
Plant-derived foods are potential vehicles for microbial antibiotic resistance genes (ARGs), which can be transferred to the human microbiome if consumed raw or minimally processed. The aim of this study was to determine the prevalence and the amount of clinically relevant ARGs and mobile genetic elements (MGEs) in differently processed smoothies (freshly prepared, cold-pressed, pasteurized and high-pressure processed) and fresh produce samples (organically and conventionally cultivated) to assess potential health hazards associated with their consumption. The MGE ISPps and the class 1 integron-integrase gene intI1 were detected by probe-based qPCR in concentrations up to 104 copies/mL in all smoothies, lettuce, carrots and a single tomato sample. The highest total (2.2 × 105 copies/mL) and the most diverse ARG and MGE loads (16/26 targets) were observed in freshly prepared and the lowest prevalences (5/26) and concentrations (4.1 × 103 copies/mL) in high-pressure-processed (HPP) smoothies. BlaCTX-M-1-15 (1.2 × 105 c/mL) and strB (6.3 × 104 c/mL) were the most abundant, and qacEΔ1 (95%), blaTEM1 (85%), ermB and sul1 (75%, each) were the most prevalent ARGs. QnrS, vanA, sat-4, blaKPC, blaNDM-1 and blaOXA-10 were never detected. HPP treatment reduced the microbial loads by ca. 5 logs, also destroying extracellular DNA potentially encoding ARGs that could otherwise be transferred by bacterial transformation. The bacterial microbiome, potential pathogens, bacterial ARG carriers and competent bacteria able to take up ARGs were identified by Illumina 16S rRNA gene sequencing. To reduce the risk of AMR spread from smoothies, our data endorse the application of DNA-disintegrating processing techniques such as HPP.